Vegetable oil aided hydrothermal synthesis of cerium oxide nanocrystals - Kim, Minsoo; Lee, Hong-shik; Shin, Young Ho; Ahn, Ki Ho; Youn, Yong-Suk; Kim, Jaehoon; Lee, Youn-Woo (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2012)
Hydrothermal synthesis of cerium oxide nanocrystals was performed with in-situ surface modification using soybean oil and palm oil as capping agents. The synthesized nanocrystals were examined by X-ray diffraction (XRD), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR) and thermogravimetric analysis (TGA). TEM results showed single crystalline nature with stable dispersion. FT-IR spectra and TGA plots further confirmed the adsorption of fatty acid molecules onto cerium oxide surface. Our findings have the advantages of reduced materials costs compared to using single component surfactants and the production of valuable by-product glycerol.